Relationship between supervisor-subordinate communication and organizational commitment in the hotel industry in Kuching, Sarawak - Ling, Siew Yeong (2000)
This study investigated the significant relationship between supervisor-subordinate factors and commitment among the employees in hotel industry in Kuching, Sarawak. In addition, the study also attempts to determine if there are differences in the level of perception toward supervisor-subordinate communication and level of commitment based on the demographic characteristics of the employees.